(untitled) (Journal of the College of Education for Women, 2019)
During the kingdom period between 1925-1958 fifty two member of parliament were elected representingHilla governorate. Only twenty nine of them were from Hilla that cause of choosing a member was according to qualifications of that era to play vole in Iraqi policy. Some of house qualifications related to tribes or privately of family. Other important causes of choosing a member depended on relationship to political parfait or holding scientific degree, in addition some members filled positions in the government such as being previous minster which gave him special distinction to be chosen as amember. Some other were members of the senate, here we should refer to the article no,63 of Iraqi constitution which imposes that any minister must not stay in the cabinet more them sir months if he was not a member in of parliament or senate council-so of the concusses in dilates did not represent their really places in order to stay in their positions as a minister in cabinet. Some others were chosen by some ministers to pass their ruler became of their personality or partialrelationship orpatronage.